Potential roles of nuclear receptors in mediating neurodevelopmental toxicity of known endocrine‐disrupting chemicals in ascidian embryos. Issue 10 (19th June 2019) - Gomes, Isa D. L.; Gazo, Ievgeniia; Besnardeau, Lydia; Hebras, Céline; McDougall, Alex; Dumollard, Rémi
Abstract: Endocrine Disrupting Chemicals (EDCs) are molecules able to interfere with the vertebrate hormonal system in different ways, a major one being the modification of the activity of nuclear receptors (NRs). Several NRs are expressed in the vertebrate brain during embryonic development and these NRs are suspected to be responsible for the neurodevelopmental defects induced by exposure to EDCs in fishes or amphibians and to participate in several neurodevelopmental disorders observed in humans. Known EDCs exert toxicity not only on vertebrate forms of marine life but also on marine invertebrates. However, because hormonal systems of invertebrates are poorly understood, it is not clear whether the teratogenic effects of known EDCs are because of endocrine disruption. The most conserved actors of endocrine systems are the NRs which are present in all metazoan genomes but their functions in invertebrate organisms are still insufficiently characterized. EDCs like bisphenol A have recently been shown to affect neurodevelopment in marine invertebrate chordates called ascidians. Because such phenotypes can be mediated by NRs expressed in the ascidian embryo, we review all the information available about NRs expression during ascidian embryogenesis and discuss their possible involvement in the neurodevelopmental phenotypes induced by EDCs. Abstract : Endocrine disrupting chemicals (EDCs) have teratogenic effects on ascidian embryos. Ascidian embryos express nuclear receptors (NRs) NRs during brain formation. EDCs known to affect these NR may exert neurodevelopmental toxicity to ascidians.